Applied satellite navigation using GPS, GALILEO, and augmentation systems - Prasad, Ramjee (Artech House mobile communications series., 2005)
"This authoritative work offers a timely, unified analysis of the various satellite navigation technologies, applications, and services in operation or development, and of the challenges that lie ahead in this rapidly evolving field."--Jacket.